Detailed chemical abundance analysis of the thick disk star cluster Gaia 1 - Koch-Hansen, Andreas; Thidemann Hansen, Terese; Kunder, Andrea (Arxiv, 2017)
Star clusters, particularly those objects in the disk-bulge-halo interface are as of yet poorly charted, albeit carrying important information about the formation and the structure of the Milky Way. Here, we present a detailed chemical abundance study of the recently discovered object Gaia 1. Photometry has previously suggested it as an intermediate-age, moderately metal-rich system, although the exact values for its age and metallicity remained ambiguous in the literature. We measured detailed chemical abundances of 14 elements in four red giant members, from high-resolution (R=25000) spectra that firmly establish Gaia 1 as an object associated with the thick disk. The resulting mean Fe abundance is $-0.62±$0.03(stat.)$±$0.10(sys.) dex, which is more metal-poor than indicated by previous spectroscopy from the literature, but it is fully in line with values from isochrone fitting. We find that Gaia 1 is moderately enhanced in the $α$-elements, which allowed us to consolidate its membership with the thick disk via chemical tagging. The cluster's Fe-peak and neutron-capture elements are similar to those found across the metal-rich disks, where the latter indicate some level of